Tafsir Kelembagaan Adaptif: Metode, Corak, dan Relevansi Al-Muntakhab dalam Konteks Kontemporer - Mafadhillah Paoziah Suhaedi; Syahrullah (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2025)
This study originates from the limited scholarly attention given to Tafsir al-Muntakhab fī Tafsīr al-Qur’an al-Karīm, an institutional tafsir compiled collectively by al-Majlis al-A‘lā li al-Syu’ūn al-Islamiyyah in Egypt. The lack of research raises both methodological and epistemological questions regarding how an institutional tafsir is designed to preserve traditional authority while simultaneously addressing the needs of modern society. The main focus of this study is to examine the methods, structure of presentation, sources, and exegetical tendencies of al-Muntakhab in order to position it within the framework of contemporary Qur’anic exegesis. Employing a qualitative-descriptive approach through textual analysis and epistemological inquiry, the findings indicate that al-Muntakhab adopts a mushafiyyah structure, accompanied by an introduction for each surah and explanatory footnotes. In terms of sources, the tafsir is largely based on bi al-ra’y, complemented in a limited way by bi al-riwayah, while its exegetical orientation reveals a distinctive combination of ‘ilmī (scientific) and adabī ijtimā‘ī (socio-ethical) approaches. The results of this research show that Tafsir al-Muntakhab is characterised by its concise, communicative, and moderate style, which distinguishes it from other institutional tafsir works in Egypt, such as al-Tafsir al-Wasīṭ consisting of fifteen volumes with extensive elaboration. This finding underscores the role of Tafsir al-Muntakhab as an adaptive, inclusive, and contextually relevant institutional tafsir that contributes significantly to the development of contemporary Qur’anic exegesis. This study recommends conducting similar research on institutional interpretations in Indonesia, involving cross-institutional collaborations to benefit the wider community.